Modification of the No-Touch Technique during Renal Artery Stenting - John A. Stathopoulos (Case Reports in Vascular Medicine)
Renal artery stenting has been established as the primary form of renal artery stenosis revascularization procedure. The no-touch technique is proposed in order to avoid renal artery injury and atheroembolism during renal artery stenting. We describe a modification of the no-touch technique by using an over-the-wire (OTW) balloon or a Quickcross catheter with a coronary wire inside, instead of the rigid  J wire. The reported technique, while it prevents direct contact of the guiding catheter with the aortic wall, at the same time it allows for a closer contact with the renal arterial ostium and a more favorable guiding catheter orientation, compared to what is achieved with the use of the more rigid  J wire, thus improving visualization, reducing the amount of contrast required, and potentially decreasing complications.